Factores asociados a sobrevida en pacientes con co-infección VIH-TBC en el Servicio de Infectología del Hospital Nacional Arzobispo Loayza, Perú, durante los años 2004-2012 - Gamboa-Acuña, Brenda (2018)
Background: The main cause of death in HIV patients is tuberculosis (TB). However, few Latin American studies have evaluated the prognosis of patients with coinfection. Aim: To determine the factors associated with survival in patients with HIV-TB coinfection treated at a Peruvian referral hospital. Methods: A retrospective cohort study was performed based on clinical records of patients treated at the Department of Infectious Diseases in the Arzobispo Loayza National Hospital from 2004 to 2012. Survival was assessed using the Kaplan-Meier estimator and Cox Proportional Hazard Model. Results: From 315 patients, 82 died during the follow-up. The mean of follow for each patient was 730 days. The multivariate analysis showed that receiving HAART (HR: 0,31; IC: 0,20-0,50; p < 0,01) and having more weight (HR: 0,96; IC 0,94–0,98; p < 0,01) when the coinfection was diagnosed, were protective factors; while having a pathology different from TB (HR: 1,88; IC: 1,19-2,98; p < 0,01), age in years (HR: 1,76; IC: 1,12-2,74; p ≤ 0,01) and being hospitalized when diagnosed with TB (HR: 1,69; IC 1,02-2,80; p < 0,04) were associated with lower survival. Discussion: Receiving HAART and having more weight when the coinfection is diagnosed were associated with a higher chance of survival.